Cover Feature: Discovery of Potent EGFR Inhibitors through the Incorporation of a 3D‐Aromatic‐Boron‐Rich‐Cluster into the 4‐Anilinoquinazoline Scaffold: Potential Drugs for Glioma Treatment (Chem. Eur. J. 13/2018). Issue 13 (8th January 2018) - Couto, Marcos; García, María Fernanda; Alamón, Catalina; Cabrera, Mauricio; Cabral, Pablo; Merlino, Alicia; Teixidor, Francesc; Cerecetto, Hugo; Viñas, Clara
Abstract : An EGFR inhibitor that incorporates closo‐ carborane has been shown to have higher affinity than erlotinib. The comparative docking analysis with compounds bearing bioisoster substructures demonstrated the relevance of the 3D aromatic boron‐rich moiety for interacting into the EGFR ATP binding region. The capability to accumulate in glioma cells, the ability to cross the blood–brain barrier and the stability under simulated biological conditions render these molecules as lead compounds for further structural modifications to obtain dual action drugs to treat glioblastoma. More information can be found in the Communication by H. Cerecetto, C. Viñas et al. onpage 3122 .